Long‐term changes in autumn migration dates at the Strait of Gibraltar reflect population trends of soaring birds. (15th November 2016) - Panuccio, Michele; Martín, Beatriz; Morganti, Michelangelo; Onrubia, Alejandro; Ferrer, Miguel
Abstract : A growing body of work shows that climate change is the cause of a number of directional shifts in the spring phenology of migratory birds. However, changes in autumn phenology are well studied and their consistency across species, as well as their link with population trends, remains uncertain. We investigate changes in the autumn migration dates of 11 species of soaring birds over the Strait of Gibraltar over a 16‐year period. Using models corrected for phylogeny, we assessed whether ecological and morphological characteristics, as well as population trends, account for interspecific shifts in migration times. We recorded different phenological changes in different periods of the migration season and suggest that these differences are due to age‐dependent responses. The variable best predicting advances in migration dates was population trend: species that did not advance their autumn migration dates were those showing a decline in their European breeding populations. We repeated our tests on a dataset representing the migration date of soaring birds across the Pyrenees Mountains and found that population trends at this site also predicted phenological shifts. Our results suggest that flexibility in migratory strategy and population trends may be related, such that different adaptive capacity in migration timing may be more relevant than other ecological traits in determining the conservation status of migratory birds in Europe and perhaps other regions.